PERAN KONSELOR DALAM MENANGANI DAMPAK PSIKOLOGIS ANAK AKIBAT PERCERAIAN ORANG TUA - Rd. Rosmianti Rahman; Djoko Nugroho (STKIP Subang, 2025)
The emergence of broken homes places children under unnecessary burdens and psychological impacts. To help children navigate the stunted growth caused by broken homes, this study examined the role of counselors in addressing the psychological impact of broken families on children. The results indicate that the presence of counselors within the community and the environment can help children improve their emotional well-being, build self-confidence, and develop social skills.